Canva-Based RESPIRA Media as an Innovation in Science Learning on the Human Respiratory System in Elementary Schools - Akhmad Sugiarto; Sendi Ramadhani; Novi Andri Nurcahyono (Jurnal Penelitian Pendidikan IPA, 2026)
This study developed RESPIRA (Respiratory Education System with Process, Interactivity, and Animation), a Canva-based learning media designed to improve fifth-grade students' attention and understanding of the human respiratory system—a challenging topic due to its abstract and complex nature. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research was conducted at SDN Sumberbendo, Lamongan Regency. Data were collected through expert validation sheets, teacher and student response questionnaires, attention surveys, and pretest-posttest assessments. Descriptive analysis, N-Gain calculations, and Wilcoxon Signed Rank Test were employed to evaluate validity, practicality, and effectiveness. Results indicated high validity (94.4%), excellent practicality ratings from teachers (97.33%) and students (95.76%), and significant effectiveness improvements. Student attention increased from 70.29% (high) to 89.67% (very high), while learning outcomes showed an average N-Gain of 0.71 (high category). The Wilcoxon test revealed significant differences between pretest and posttest scores (p < 0.001). RESPIRA media proved valid, practical, and effective for elementary science education, successfully enhancing attention and conceptual understanding through interactive, engaging, and contextually appropriate learning experiences aligned with student characteristics.